THE EFFECTIVENESS OF USING SHADOW READING IN TEACHING ENGLISH INTONATION - Kristanti, Ika Lusi (JEELL (Journal of English Education, Linguistics and Literature), 2017)
Teaching second language learners encourages lecturer to show up their creativity in class. For example: they can use new technique by considering need analysis, such as: using shadow reading in teaching English. Shadow reading is one of teaching technique applied in teaching English, especially teaching English intonation. Because intonation plays crucial part in conveying ideas, feeling, and information to other. Besides, considering pitch movement, second language learners also must consider the expresiveness and articulacy in English. The phenomenon encourages the researcher to conduct this study on teaching English intonation by using shadow reading. In this study, the researcher is eager to find the effectiveness of using shadow reading in teachingEnglish intonation. The researcher takes the first semester students of STKIP PGRI Jombang as the subject of this research. This study uses quasi experimental design. It is designed by using test, mainly: pre-test and post-test. The result of this study shows that using shadow reading is effective in teaching English Intonation. Through shadow reading, lecturer can bring hilarious atmosphere into the class of second language learners. It also can increase second language learners’ ability in using English intonation correctly